Injury prevention knowledge, beliefs and strategies in elite female footballers at the FIFA Women's World Cup France 2019 - Geertsema, C.; Geertsema, L.; Farooq, A.; Harøy, J.; Oester, C.; Weber, A.; Bahr, R. (British Journal of Sports Medicine, 2021)
OBJECTIVES This study assessed knowledge, beliefs and practices of elite female footballers regarding injury prevention.